دور الاتصال في دعم انـخراط الشباب في الوسط المهنـي - هلوب طاهر; د/عطاء الله طريف (جامعة عمار ثليجي الاغواط, 2023)
ملخص: تهدف هذه الدراسة بتعرف على دور الاتصال في دعم الانخراط الشباب في الوسط المهني وهي عبارة عن دراسة ميدانية في إحدى المؤسسات الحرفية والمعروفة بغرفة الصناعة التقليدية والحرف، حيث سعت هذه الدراسة إلى الإجابة عن التساؤل العام الذي كان كالآتي: ما مدى فعالية دور الاتصال في دعم انخراط الشباب في الوسط المهني بالغرفة الصناعة التقليدية والحرف بالأغواط. وللإجابة عن التساؤلات تم الاعتماد على المنهج الوصفي من خلال الاستخدام الميداني، يتكون المجتمع الدراسة من المنخرطين بغرفة صناعة التقليدية والحرف بالأغواط، وتم لاعتماد في هذه الدراسة على أداتين لجمع البيانات وهي المقابلة مع الموظفين بغرفة الصناعة التقليدية والحرف، وبالإضافة لأداة الاستبيان، وكذا تم لاعتماد على أسلوب الحصر الشامل لمفردات الدراسة بغرفة الصناعة التقليدية والحرف بالأغواط التي تزامنت مع دورة شهر ماي2023 لتكوين المنخرطين بغرفة الصناعة التقليدية والحرف للولاية، البالغ عددهم 58 مفردة. وقد تم لاعتماد على 50 مبحوثا، إذ وزع عليهم الاستبيان حيث تضمن مجموعة من الأسئلة ذات العلاقة بأسئلة وأهداف الدراسة. توصلت الدراسة لعديد من النتائج أهمها أن غالبية شباب المنخرطين راض على تقنيات الاتصال المستخدمة بغرفة الصناعة التقليدية والحرف لدعم انخراط الشباب مما تمتاز بالمرونة والتسيير بشكل جيد، ويعمل الاتصال على تسهيل عملية تبادل الأفكار وعلى خلق جو الانسجام وبعث الحور والتفاهم وما يعكس تقديم خدمات ودعائم جيدة التي ترفع سمعة غرفة الصناعة التقليدية والحرف بالأغواط. Abstract : This study aims to identify the role of communication in supporting the involvement of young people in the professional community. It is a field study in one of the craft institutions known as the Chamber of Handicrafts and Crafts. Young people in the professional circle in the Chamber of Traditional Industry and Crafts in Laghouat. In order to answer the questions, the descriptive approach was relied on through field use. The study community consisted of those involved in the Chamber of Traditional Industry and Crafts in Laghouat. In this study, two tools were adopted to collect data, which is the interview with the employees of the Chamber of Traditional Industry and Crafts, in addition to the questionnaire tool. The method of comprehensive enumeration of the study vocabulary in the Chamber of Handicrafts and Crafts in Laghouat, which coincided with the May 2023 session to train those enrolled in the Chamber of Handicrafts and Handicrafts of the state, numbering 58 items. It was based on 50 respondents, as the questionnaire was distributed to them, as it included a set of questions related to the questions and objectives of the study. The study reached a number of results, the most important of which is that the majority of the young participants are satisfied with the communication techniques used in the Chamber of Traditional Industry and Crafts to support the involvement of young people, which is characterized by flexibility and good management. Raising the reputation of the Chamber of Handicrafts and CraftLs in aghouat
دارسة ميدانية على عينة من المنخرطين بغرفة الصناعة التقليدية والحرف بالأغواط